Bioetika dan Transformasi Fiqh Kontemporer di Era Teknologi Medis Modern - Muhammad Habib Adi Putra (Institut Agama Islam Sunan Giri Ponorogo, 2026)
The advancement of modern medical technologies such as health-related artificial intelligence, organ transplantation, neurotechnology, and assisted reproductive technologies has transformed the paradigm of healthcare services while simultaneously giving rise to complex new bioethical challenges in modern society. This situation creates tension between the development of global health ethics based on autonomy, human dignity, and patient rights and the classical fiqh constructions, which tend to be normative-textual. This study aims to analyze the transformation of contemporary fiqh in responding to the developments in bioethics during the era of modern medical technology through an interdisciplinary approach combining Islamic law, maqashid al-shariah, and medical ethics. The study employs a qualitative method with a normative-interdisciplinary approach through documentation studies of scientific journals, fatwas, academic books, and international organizational documents. The research findings indicate that the development of modern medical technology drives a methodological transformation in fiqh from a textual approach to an approach based on the objectives of sharia, public interest, and Islamic bioethics that is more humanistic and contextual. This study concludes that Islamic bioethics is a strategic instrument in maintaining the relevance of contemporary fiqh and recommends strengthening a multidisciplinary approach in formulating modern health law.